2016
DOI: 10.1149/2.1111610jes
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Li-Ion Conductivity of LiGa1xAlxGeO4Phenacite Compounds with 0 ≤x≤ 1

Abstract: Compounds of LiGa 1−x Al x GeO 4 with 0 ≤ x ≤ 1 were examined using powder X-ray diffraction measurements and electrochemical impedance spectroscopy, to clarify their structures and Li-ion conductivity (σ Li ) as a function of x, and to compare with those for a wide variety of AB 2 O 4 -type oxides. The x = 0 and 0.25 samples were found to exhibit a phenacite structure with R 3 space group, whereas the x ≥ 0.5 samples were found to exhibit an ordered phenacite structure with R3 space group due to the 1:1 catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The present QENS spectrometer (resolution ∼μeV) can capture the diffusion dynamics of ∼1 × 10 −10 m 2 /s or conductivity of ∼mS cm −1 . The ionic conductivity measurements 28 show a conductivity of 2 × 10 −2 mS cm −1 at 973 K, which is well below the QENS accessible value of ∼mS cm −1 , which means that the Li hopping between different sites is extremely slow. Most interestingly, the large stochastic motion localized within the cavities is well capture by QENS, which also gives important information about the dynamics and validates the simulations.…”
Section: Quasi Elastic Neutron Scattering (Qens)mentioning
confidence: 84%
See 4 more Smart Citations
“…The present QENS spectrometer (resolution ∼μeV) can capture the diffusion dynamics of ∼1 × 10 −10 m 2 /s or conductivity of ∼mS cm −1 . The ionic conductivity measurements 28 show a conductivity of 2 × 10 −2 mS cm −1 at 973 K, which is well below the QENS accessible value of ∼mS cm −1 , which means that the Li hopping between different sites is extremely slow. Most interestingly, the large stochastic motion localized within the cavities is well capture by QENS, which also gives important information about the dynamics and validates the simulations.…”
Section: Quasi Elastic Neutron Scattering (Qens)mentioning
confidence: 84%
“…However, Al and Ge have random distribution at two nonequivalent 9b sites with 50% occupancy of each of Al and Ge. A later study by Mukai et al 28 on LiGa 1−x Al x GeO 4 (LGAGO) (0 ≤ x ≤ 1) has shown that LAGO has a highly ordered hexagonal phenacite structure (space group, R3) with the same lattice parameters as determined by Fleet et al 38 Recently, Yang et al 48 confirmed that LAGO has the ordered hexagonal-phenacite structure (space group R3). The crystal structure of ordered hexagonal phenacite LiAlGeO 4 is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations